2021
DOI: 10.1002/jaba.850
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the function of social interaction for children with autism

Abstract: Several researchers have assessed whether or not social interaction is reinforcing; however, few studies have evaluated methods of assessing whether social interactions function as reinforcing, neutral, or aversive stimuli. We extend this research by evaluating a new method of assessing the function of social interaction. Twenty-one children diagnosed with Autism Spectrum Disorder (ASD) participated. Social interactions were found to function as reinforcers for 9 participants, neutral stimuli for 7 participant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
54
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 11 publications
(56 citation statements)
references
References 24 publications
2
54
0
Order By: Relevance
“…The experimenters evaluated whether there was a difference in the reinforcing value of social stimuli for children with ASD compared to their typically developing peers. Similar to Call et al (2013) and Morris and Vollmer (2020b, 2021), the results revealed that participants with and without ASD worked harder for access to items and social stimuli as compared to the solitary items in a progressive ratio (PR) assessment, which reveals the influence social interaction may have on participant preference for the leisure items included.…”
supporting
confidence: 82%
See 2 more Smart Citations
“…The experimenters evaluated whether there was a difference in the reinforcing value of social stimuli for children with ASD compared to their typically developing peers. Similar to Call et al (2013) and Morris and Vollmer (2020b, 2021), the results revealed that participants with and without ASD worked harder for access to items and social stimuli as compared to the solitary items in a progressive ratio (PR) assessment, which reveals the influence social interaction may have on participant preference for the leisure items included.…”
supporting
confidence: 82%
“…Another variable that may influence the results of the SPA is whether social interaction (e.g., praise, conversation, physical attention; Vollmer & Hackenberg, 2001) is provided along with the delivery of the item or activity during the access period. A recent series of studies utilized a time allocation procedure to evaluate the function of social interaction for young children with autism spectrum disorder (ASD; Call et al, 2013; Morris & Vollmer, 2020b, 2021). All three studies measured the duration of time participants spent on either side of a room divided into two, with each side containing similar (or identical) leisure items.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, that same methodology has been extended to the identification of preferred types of social interactions that are likely to function as reinforcers (e.g., Kelly et al, 2014; Morris & Vollmer, 2019). However, recent research has also developed and evaluated methods of assessing the function of generic, nonindividualized social interactions or social interaction in general (Call et al, 2013; Morris & Vollmer, 2020d, 2021). Such methods, which we will term assessments of sociability, serve a function that is distinct from those that identify preferred, individualized items or interactions.…”
mentioning
confidence: 99%
“…Assessments of sociability are designed to emulate these naturalistic conditions. In such assessments (Call et al, 2013; Morris & Vollmer, 2020d, 2021) the experimenter delivers only generic descriptions of the environment (e.g., “It looks like you are having fun with the blocks.”) and positive, praise‐like statements (e.g., “Wow, that is so cool!”). Experimenters avoid prompting or initiating more specific, individualized types of play or interaction unless the client mands for them.…”
mentioning
confidence: 99%